Phytoplankton Community Structure in Seagrass Beds of Nain Island Waters - Mokosuli, Febrianty Dhea; Rimper, Joice R.T.S.L; Warouw, Veibe; Wullur, Stenly; Losung, Fitje; Mokolensang, Jeffrie F. (Jurnal Ilmiah Platax, 2024)
This study aims to identify phytoplankton species, calculate phytoplankton abundance, diversity index, uniformity index, phytoplankton dominance index, and determine environmental conditions such as temperature, pH, salinity, nitrate, and phosphate in the seagrass ecosystem of Nain Island Waters. Sampling includes seawater for the needs of phytoplankton identification measurement of nitrate and phosphate levels and measurement of water parameters in situ. Phytoplankton sampling is done horizontally using a plankton net. Phytoplankton identification found in the seagrass ecosystem of Nain Island Waters consisted of four classes, namely Bacillariophyceae (Rhizosolenia sp.; Nitzschia sp.; Chaetoceros sp.; Navicula sp.; Eucampi sp.; Pleurosigma sp.; Thalassionema sp.; Melosira sp.), Dinophyceae (Ceratium sp.; Protoperidinium sp.), Chlorophyceae (Spirogyra sp.), and Euglenophyceae (Euglena sp.). The calculation of phytoplankton abundance is in the range of 9 - 51 cells/l. The highest abundance was found at station one which was 51 cells/l, then station three which was 21 cells/l, and station two which was 9 cells//I. The diversity index is in the range of 0.8749 - 1.8668 which means there is community instability. The uniformity index is in the range of 0.2226 - 0.8460, while the dominance index is in the range of 0.2060 - 0.6093, this indicates that the water conditions are stable. Environmental conditions (temperature, salinity, pH, nitrate, and phosphate) in the seagrass ecosystem of Nain Island Waters are still quite good for phytoplankton growth. Keywords: Phytoplankton, Seagrass, Nain Island, Abundance, Biological Index Abstrak Penelitian ini bertujuan untuk identifikasi jenis-jenis fitoplankton, menghitung kelimpahan fitoplankton, indeks keanekaragaman, indeks keseragaman, indeks dominasi fitoplankton dan mengetahui kondisi lingkungan seperti suhu, pH, salinitas, nitrat, dan fosfat di ekosistem padang lamun Perairan Pulau Nain. Pengambilan sampel meliputi air laut untuk kebutuhan identifikasi fitoplankton dan pengukuran kadar nitrat dan fosfat perairan serta pengukuran parameter perairan secara In situ. Pengambilan sampel fitoplankton dilakukan secara horizontal dengan menggunakan plankton net. Fitoplankton yang ditemukan terdiri dari empat kelas yaitu Bacillariophyceae (Rhizosolenia sp. Nitzschia sp. Chaetoceros sp. Navicula sp. Eucampi sp. Pleurosigma sp. Thalassionema sp. Thalassionema sp. Melosira sp.), Dinophyceae (Ceratium sp. Protoperidinium sp.), Chlorophyceae (Spirogyra sp), dan Euglenophyceae (Euglena sp). Hasil perhitungan kelimpahan fitoplankton berada di kisaran 9 - 51 sel/l. Kelimpahan tertinggi ditemukan pada stasiun satu yaitu 51 sel/l, kemudian stasiun tiga yaitu 21 sel/l dan stasiun dua yaitu 9 sel/I. Indeks keanekaragaman berada pada kisaran 0,8749 - 1,8668 yang berarti adanya ketidakstabilan komunitas. Indeks keseragaman yaitu pada kisaran 0,2226 - 0,8460, sedangkan indeks dominasi berada pada kisaran 0,2060 - 0,6093, hal ini menunjukkan kondisi perairan dalam keadaan stabil. Kondisi lingkungan (suhu, salinitas, pH, nitrat dan fosfat) di ekosistem padang lamun Perairan Pulau Nain masih cukup baik untuk pertumbuhan fitoplankton. Kata kunci: Fitoplankton, Padang Lamun, Pulau Nain, Kelimpahan, Indeks Biologi